Pengaruh Modal dan Biaya Produksi Terhadap Pendapatan PT Minang Sukses Sejahtera - Muhammad Hafiz; Alpon Satrianto (Universitas Negeri Padang, 2022)
This study aims to determine the effect of capital and production costs on the income of PT Minang Sukses Sejahtera. This type of research is quantitative in nature using secondary data in the type of time series data from January 2019 to December 2021 as many as 36 data. The data collection technique is documentation. Using multiple linear regression analysis method. The results of the study concluded that the capital variable had a positive and significant effect on the income of PT Minang Sukses Sejahtera and the production cost variable had a positive and significant effect on the income of PT Minang Sukses Sejahtera. Capital and production costs simultaneously have a positive and significant impact on the income of PT Minang Sukses Sejahtera. Based on the findings in this study, it is suggested to PT Minang Sukses Sejahtera to be able to manage capital and production costs effectively and efficiently so as to maximize revenue and minimize losses so that the company can continue to grow and survive.